1986
DOI: 10.1139/z86-084
|View full text |Cite
|
Sign up to set email alerts
|

Scent rubbing in wolves (Canis lupus): the effect of novelty

Abstract: Two groups of wolves (Canis lupus) (N = 15 individuals) were tested for scent rubbing with eight novel odours from four classes of scent (herbivore, carnivore, food, and manufactured). If novelty is the primary factor influencing scent rubbing, we expected high initial rubbing frequencies across classes that would decline with successive presentations. Differential responses would indicate class of scent is more important. The wolves exhibited a striking propensity to scent rub differentially among odours. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Scent-marking serves to communicate territories among conspecifics, and resident coyotes and wolves strategically mark via urination and defecation at higher rates than do transients, with alpha pairs often exhibiting the highest defecation rates among all cohorts (Rothman and Mech 1979, Gese and Ruff 1997, Barja and List 2014. In contrast, rubbing behavior by canids has been attributed to mate attraction and early courtship, suggesting that rubbing in odorous materials would be advantageous to transients who are actively seeking mates (Ryon et al 1986, Martin and Farge 1988, Heffernan et al 2007). Therefore, we speculate that scat sampling may be more likely to detect territorial alpha pairs and other residents, whereas hair sampling may be more likely to detect transients, which would cause the inconsistent individual heterogeneity between detection methods that we found.…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Scent-marking serves to communicate territories among conspecifics, and resident coyotes and wolves strategically mark via urination and defecation at higher rates than do transients, with alpha pairs often exhibiting the highest defecation rates among all cohorts (Rothman and Mech 1979, Gese and Ruff 1997, Barja and List 2014. In contrast, rubbing behavior by canids has been attributed to mate attraction and early courtship, suggesting that rubbing in odorous materials would be advantageous to transients who are actively seeking mates (Ryon et al 1986, Martin and Farge 1988, Heffernan et al 2007). Therefore, we speculate that scat sampling may be more likely to detect territorial alpha pairs and other residents, whereas hair sampling may be more likely to detect transients, which would cause the inconsistent individual heterogeneity between detection methods that we found.…”
Section: Notesmentioning
confidence: 99%
“…Both coyotes and wolves tend to be highly territorial and strategically defecate to mark and communicate territory extents to conspecifics (Rothman and Mech 1979, Gese and Ruff 1997, Barja and List 2014; therefore, collecting scat samples along travel routes or at rendezvous sites has proven effective , Morin et al 2016, Piaggio et al 2016, L opez-Bao et al 2018). Furthermore, rubbing in odorous materials, such as carcasses of dead wildlife, is a natural behavioral response of canids (Ryon et al 1986, Martin and Farge 1988, Heffernan et al 2007, and collecting hair from lured ground-based rub pads has been used to detect both wolves and coyotes (Ausband et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…First, hanging devices may have been less secure than ground-based devices; thus, the device moved with the coyote while it rubbed and, therefore, no hair was captured. Second, strong scents incite rub and rub behavior, which is a behavior more naturally performed on the ground by lowering a shoulder and rubbing the neck or shoulders (Ryon et al 1986). Ground devices were more productive for collecting samples, although differences in behavior by individual coyotes Ruff 1997, Darrow andShivik 2009) may result in some coyotes only being detected by hanging devices.…”
Section: Discussionmentioning
confidence: 99%
“…Coyotes have been shown to rub in lures containing chemicals that mimic degradation and fermentation of tissues, and rub behavior has been elicited from wolves using novel and malodorous substances (Ryon et al 1986, Asa and Mech 1995, Kimball et al 2000. In addition, biologists in the northern Rockies of the United States have observed wolves rubbing in a variety of commercial lures commonly used for trapping (L. Bradley, Montana Fish, Wildlife and Parks, personal communication; M. Jimenez, United States Fish and Wildlife Service, personal communication).…”
mentioning
confidence: 99%
“…Hyenas show a preference for rolling in animal-based odors, and receive more attention from conspecifics when smelling of carrion (Drea et al, 2002 ). Ryon et al ( 1986 ) found that wolves preferred to rub themselves in strong-smelling, manufactured odors (perfume and motor oil) above carnivore odors, and that sheep and horse feces did not elicit rubbing in wolves. Among the causal explanations for these observed behaviors is status advertisement, where dominant animals seek to stand out by adding complexity to and increasing the range of their odorous presence (Gosling and McKay, 1990 ).…”
Section: What Is Wrong With the Current View And Terminology?mentioning
confidence: 99%